Studi Mengenai Pelanggan Yang Membeli Dari Perusahaan Multi-Level Marketing Di Jakarta - William Indrajaya (Universitas Tarumanagara, 2019)
Multi-level Marketing (MLM), also known as network marketing is a relatively grown industry with its size and reputation are growing rapidly. According to the Direct Selling Association (DSA), direct selling is a US 183 billion industry worldwide with an annual growth rate at 2 percent. Multi-level Marketing was brought to Indonesia from the US over a decade ago and has been growing for almost a decade here in indonesia. It unique operating format seems to contravene all traditional sales principles. In Indonesia , the number of sales which was generated by people who involved in direct selling almost hit the 1.2 billion mark. According to WFDSA (2016), total distributor who have join the Multi-level Marketing business in indonesia is around 14 million. These member are people who join Multi-level Marketing company as their full time job and some of them as their part-time job. This study surveys 200 customers in Indonesia area concerning their motivation of buying from MLM company, their demographic characteristic and teir attitudes as consumers towards MLM products. In addition we also compare the consumer satisfaction of MLM products to that of the similar products on traditional market. The result shown that the major factor of purchasing MLM Product is because pressure from friend or relatives and the product special function. I also found that skin care and supplements is the most initial buying and rebuying categories in the MLM Industries. Major faction that influence customer satisfaction on MLM Products is product quality, refundable, after sales services, corporation reputation, brand reputation, delivery speed, and payment variety.